PEMANFAATAN UML (UNIFIED MODELING LANGUAGE) DALAM PERANCANGAN SISTEM INFORMASI REKAM MEDIS SEDERHANA PADA KEGIATAN POSBINDU PTM - Sis Churin Ien Aulia (Teknik Informatika Fakultas Ilmu Komputer, 2022)
The Integrated Non-Communicable Diseases Development Post (Posbindu NCD) is a form of health empowerment and public knowledge about non-communicable diseases that have a greater risk. In this Posbindu NCD, of course there are activities and steps that have been determined. The purpose of this study was to determine the concept of Posbindu NCD itself and the use of UML (Unified Modelling Language) to develop a simple medical record information system. The use of UML is done because in the characteristics of UML there is the possibility of identification of any objects that affect the system. The research method used is literature review and interviews with cadres on duty. Meanwhile, the journal criteria used are in the 2011-2020 range. The results of this study indicate that Posbindu NCD is very useful for early detection of non-communicable diseases and the use of UML to develop a simple medical record information system is very efficient.)